Автоматизація складання програм тренування та обліку їх виконання для спортсменів - Сусла, В. О. (ХНУРЕ, 2023)
The main purpose of this article is to define the features of a future information system that will help to facilitate interactions between trainers and clients, create training programs, and track their completion. The article contains an analysis of existing systems and apps, including their advantages and disadvantages. The future system must be convenient for end-users and be able to satisfy all of their needs.